RhoE promotes metastasis in gastric cancer through a mechanism dependent on enhanced expression of CXCR4. - Bin Feng; Kai Li; Haixing Zhong; Gui Ren; Hefei Wang; Yulong Shang; Ming Bai; Jie Liang; Xin Wang; Daiming Fan (PLoS ONE, 2013)
RhoE, a novel member of the Rho protein family, is a key regulator of the cytoskeleton and cell migration. Our group has previously shown that RhoE as a direct target for HIF-1α and mediates hypoxia-induced epithelial to mesenchymal transition in gastric cancer cells. Therefore, we assumed that RhoE might play an important role in gastric cancer metastasis. In the present study, we have explored the role of RhoE expression in gastric cancer, cell invasion and metastasis, and the influence of RhoE on regulating the potential expression of down-stream genes. RhoE expression was elevated in gastric cancer tissues as compared with normal gastric tissues. We also found a close correlation between the histological grade and the diagnosis of the patient. Up-regulation of RhoE significantly enhanced the migratory and invasive abilities of gastric cancer cells both in vitro and in vivo. Moreover, down-regulation of RhoE diminished the metastatic potential of cancer cells. PCR array and subsequent transwell assay showed that the regulation of gastric cancer metastasis by RhoE was partially mediated by CXCR4. This observation suggested that CXCR4 might be a downstream effector for RhoE. In summary, our study identified RhoE as a novel prognostic biomarker and metastatic-promoting gene of gastric cancer.